Analisa Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Untuk Meningkatkan Minat Pembelian Ulang Pada Rumah Makan Lombok Idjo - Muryanto Agus Nuswantoro; Emy Susiatin; Juhanes Juhanes (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The purpose of this study was to analyze the effect of Service Quality on Consumer Satisfaction in order to increase Repurchase Interest in Lombok Idjo Restaurant located on Jl. Majapahit No.412, Palebon, Pedurungan District, Semarang City. The population in this study were consumers or visitors totaling 105 people. The results of hypothesis testing of research data from visitors who have been collected and analyzed with AMOS, from the relationship between research variables where p < 0.05 obtained, namely the tangible variable (X1) has a positive, significant effect on the consumer satisfaction variable (Y1), where the CR value is 2.732> 1.97 and the P-value is 0.006 < 0.05. The reliability variable (X2) has a positive, insignificant effect on the customer satisfaction variable (Y1) where the CR value is 2.026> 1.97 and the P-value is 0.043> 0.05. The responsiveness variable (X3) has no effect on customer satisfaction (Y1) at Lombok Idjo Restaurant where the CR value is 1.239 < 1.97. The tangible variable has no effect on repurchase interest (Y2) at Lombok Idjo Restaurant where the CR value is 0.856 < 1.97. The reliability variable (X2) has a positive, significant effect on the repurchase interest variable (Y2) where the CR value is 3.095> 1.97 and the P-value is 0.002 <0.05. The responsiveness variable (X3) has a positive, insignificant effect on the repurchase interest variable (Y2) where the CR value is 2.043> 1.97 and the P-value is 0.041> 0.05. The consumer satisfaction variable (Y1) has a positive, significant effect on the repurchase interest variable (Y2) where the CR value is 3.228> 1.97 and the P-value is 0.001 <0.05.